2019
DOI: 10.1021/jacs.8b10910
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Single-Atom Ni1 and Ru1 Sites on CeO2 for Dry Reforming of CH4

Abstract: Heterogeneous catalysis performs on specific sites of a catalyst surface even if specific sites of many catalysts during catalysis could not be identified readily. Design of a catalyst by managing catalytic sites on an atomic scale is significant for tuning catalytic performance and offering high activity and selectivity at a relatively low temperature. Here, we report a synergy effect of two sets of single-atom sites (Ni1 and Ru1) anchored on the surface of a CeO2 nanorod, Ce0.95Ni0.025Ru0.025O2. The surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
188
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(207 citation statements)
references
References 48 publications
(86 reference statements)
2
188
1
2
Order By: Relevance
“…In light of the thermodynamic stability of CH 3 to subsequent C–H cleavage over our catalysts, the appearance of CO as a major product in our catalytic system appears paradoxical. However, a recent report of DRM over Ni 4 clusters (which also show good carbon deposition resistance 52 ) identified the oxidation of CH 3 to CH 3 O as an alternative route to CO following initial methane activation, as also proposed for Ni 1 –Ru 1 /CeO 2 42 . We therefore considered this alternative route for transforming reactively formed CH 3 to CO without carbon deposition (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In light of the thermodynamic stability of CH 3 to subsequent C–H cleavage over our catalysts, the appearance of CO as a major product in our catalytic system appears paradoxical. However, a recent report of DRM over Ni 4 clusters (which also show good carbon deposition resistance 52 ) identified the oxidation of CH 3 to CH 3 O as an alternative route to CO following initial methane activation, as also proposed for Ni 1 –Ru 1 /CeO 2 42 . We therefore considered this alternative route for transforming reactively formed CH 3 to CO without carbon deposition (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Recent elegant work by Tang et al 42 reported a synergy between single-atom Ru 1 and Ni 1 sites resulting in very high activity for DRM even at 600 °C. Significant performance benefits accrued for our catalytic system under identical reaction conditions, even for loadings that do not exclusively give rise to single atoms: the 2 wt% Ni 1 /HAP-Ce catalyst delivered similar activity and superior stability (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thea tomic active centers mentioned above possess only one type of single atoms.Iftwo or more types of single-metal atoms are introduced, an enhanced HER performance may be expected. [195][196][197][198] In two-metal active centers,o ne kind of metal atom may modify the electronic structure of the other to enhance the HER activity. [199] We [200] synthesized uniformly dispersed Cu-Pt sites on Pd nanorings (NRs;F igure 9a,b) by at wo-step wet chemical method.…”
Section: Active Centers With Twod Ifferent Metal Atomsmentioning
confidence: 99%
“…Furthermore, the current research focusing on biomedical applications of SACs mainly concentrates on cancer treatment, wound disinfection, biosensing, and oxidative‐stress cytoprotection, while other biomedical applications including diagnosis, multimodal imaging, inflammation alleviation as well as Alzheimer's disease, Parkinson's disease, and diabetes treatment are rarely studied. In addition, although numerous SACs have been successfully fabricated, including diverse single metal atoms (Au, Co, Fe, Ir, Ru, Pt, Pd, etc.) on various supports such as N‐doped carbon, metal oxides, and layered double hydroxides, only Fe‐, Au‐, Zn‐, and Cu‐based SACs, especially M‐N‐C nanostructures, have been demonstrated their potential in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%